Implementation of multicultural values in the curriculum of the islamic education management study program - tria ina utari (IKIP PGRI Pontianak, 2023)
Multicultural education is an effort to integrate the nation as a manifestation of Indonesia's diverse socio-cultural conditions. The purpose of this study was to determine the implementation of curriculum development based on multicultural values. This study uses a qualitative approach. Data collection uses primary data and secondary data. To check the validity of the data so that the level of trustworthiness, transferability, reliability and comparability can be tested, it is used to check the validity of the data, namely credibility, transferability, dependability, and conformability. The results show that curriculum management in the Islamic education management study program by integrating multicultural values is carried out through the stages of planning, implementing, monitoring and reviewing the curriculum. Lecturers are given space to develop multiculturalism according to the subjects being taught, so that exclusivity and gaps that trigger conflict can be reduced